Deciphering the synergism of endogenous glycoside hydrolase families 1 and 9 from Coptotermes gestroi - Franco Cairo, João Paulo L.; Oliveira, Leandro C. [UNESP]; Uchima, Cristiane A.; Alvarez, Thabata M.; Citadini, Ana Paula da S.; Cota, Júnio; Leonardo, Flávia Costa; Costa-Leonardo, Ana M. [UNESP]; Carazzolle, Marcelo F.; Costa, Fernando F.; Pereira, Gonçalo A.G.; Squina, Fabio M. (Elsevier, 2013)
Termites can degrade up to 90% of the lignocellulose they ingest using a repertoire of endogenous and symbiotic degrading enzymes. Termites have been shown to secrete two main glycoside hydrolases, which are GH1 (EC 3.2.1.21) and GH9 (EC 3.2.1.4) members. However, the molecular mechanism for lignocellulose degradation by these enzymes remains poorly understood. The present study was conducted to understand the synergistic relationship between GH9 (CgEG1) and GH1 (CgBG1) from Coptotermes gestroi, which is considered the major urban pest of São Paulo State in Brazil. The goal of this work was to decipher the mode of operation of CgEG1 and CgBG1 through a comprehensive biochemical analysis and molecular docking studies. There was outstanding degree of synergy in degrading glucose polymers for the production of glucose as a result of the endo-β-1,4-glucosidase and exo-β-1,4-glucosidase degradation capability of CgEG1 in concert with the high catalytic performance of CgBG1, which rapidly converts the oligomers into glucose. Our data not only provide an increased comprehension regarding the synergistic mechanism of these two enzymes for cellulose saccharification but also give insight about the role of these two enzymes in termite biology, which can provide the foundation for the development of a number of important applied research topics, such as the control of termites as pests as well as the development of technologies for lignocellulose-to-bioproduct applications. © 2013 Elsevier Ltd.
Keywords: APTS; BIN; CD; CMC; Coptotermes gestroi; CZE; DNS; DS; GH; Glycoside hydrolase; GOD; IMAC; Molecular docking; P-NP; PASB; Synergistic interaction; Termite